Risk-based evaluation for underground mine planning - Maybee, Bryan; Fava, L. (Gecamin, 2011)
As underground mine planning tools become more sophisticated, mine planners have the capacity to investigate numerous mine sequencing options to identify the best strategy for a given project, creating higher value for shareholders. The information required for mine planning decisions goes beyond the external sources of uncertainty recognised by typical evaluation techniques used in the mining industry, to include technical factors (e.g. mine development layout) and the ability of a mineral extraction project to achieve planned production levels. Due to the individual characteristics that define underground mining projects, each will exhibit its individual risk profile, and thus advanced evaluation techniques must capture this information.This paper describes a Risk‐based Evaluation Methodology that accounts for financial and technical scheduling risk in the evaluation of underground mining projects. It provides decision‐makers with more information early in the mine planning cycle by combining planning and design methodologies with evaluation techniques to identify, optimise and evaluate strategies for mining extraction sequences. Standard evaluation practices used in the mining industry (Discounted Cash Flow, Real Options and Monte Carlo Simulation) are combined with the concepts of Modern Portfolio Theory to establish an evaluation methodology that recognises financial uncertainty in the context of technical scheduling factors. This paper will show that the Risk‐based Evaluation Methodology can be used at the tactical level, as it is applied in combination with the Schedule Optimisation Tool (SOT), for the purpose of recommending a materials handling system to be implemented in a mining project. For the case study, the inclusion of more information in the decision‐making process not only provides a more accurate valuation and allows for the recognition of risk, but it also alters the ultimate decision.